Optimization of descent trajectories for lunar base settlement - Boere, M. (author) (2010)
Four decades after Neil Armstrong's 1st steps on the Moon the time has come to take it one step further, the permanent occupation of humans on lunar soil. Permanent occupation of humans will revive the dream of exploring space and will open the doors for space flight to Mars or even further. For this reason this project investigates the possibilities of placing a base on the South Pole of the Moon before July 1, 2020. The South Pole has been chosen for several reasons, although the main reason is the recently discovered presence of water by NASA's LCROSS mission in 2009. The base itself consists of four modules made of an inflatable structure to minimize for weight. The following research question was set at the beginning of this study, Is it possible with the current technology to establish a permanent manned base on the South Pole of the Moon before July 1, 2020? This project was setup by ESA and is a joined effort of three students of the Delft University of Technology, Antonio Pagano, Valentio Zuccarelli and myself. The mission itself is therefore also divided into three parts, the Earth ascent, the Earth-Moon trajectory and the descent to the lunar surface. This study will focus on the last part, the design of the lunar descent trajectories. The goal of this study is, Design of the optimal lunar descent trajectory with the goal of constructing a permanent base on the lunar South Pole. This project assumed that the launchers Ares-I and Ares-V are available for the lunar base mission, as well as Constellation's lander Altair. The descent trajectory is optimized for maximum payload that can be brought to the lunar surface. The descent starts at the end of the Earth-Moon trajectory, a 100 km altitude, 89.8 deg inclination circular parking orbit. The following three different methods are used to study the descent trajectory and are compared at the end: dividing the descent into intervals, indirect method and gravity-turn trajectory. By using the indirect method the biggest payload mass can be brought to the ...